2007
DOI: 10.1115/1.2221328
|View full text |Cite
|
Sign up to set email alerts
|

Coupling Vibrations in Rotating Shaft-Disk-Blades System

Abstract: Applications that have coupling among shaft, disk, and blades are investigated. A shaft-disk-blades unit often seen in engineering is presented. The governing relations for shaft torsion, disk bending, and blade bending are derived. Free vibration is then studied and the results show that shaft-blade (SB), shaft-disk-blades (SDB), disk-blades (DB), and blade-blade (BB) type coupling modes exist. The SDB and DB modes are observed to be evolved from the original SB and BB modes in a previously studied case of a … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
20
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 25 publications
1
20
0
Order By: Relevance
“…Chiu and Chen 3 and Chiu and Yang 4 presented the coupled vibration responses of rotating rotor system with different disks by means of numerical simulations. Yang and Huang 5,6 investigated the free vibration of coupling components including shaft-torsional, disk transverse and blade bending by utilizing an energy method. Jeon et al 7 developed the rotordynamic model of fuel turbopump and performed the dynamic analysis to predict rotating natural frequencies, critical speeds and system instability.…”
Section: Introductionmentioning
confidence: 99%
“…Chiu and Chen 3 and Chiu and Yang 4 presented the coupled vibration responses of rotating rotor system with different disks by means of numerical simulations. Yang and Huang 5,6 investigated the free vibration of coupling components including shaft-torsional, disk transverse and blade bending by utilizing an energy method. Jeon et al 7 developed the rotordynamic model of fuel turbopump and performed the dynamic analysis to predict rotating natural frequencies, critical speeds and system instability.…”
Section: Introductionmentioning
confidence: 99%
“…It can overcome the difficulty of obtaining the collision force in the contact process in the transient impact model and the difficulty of selecting parameters in the continuous contact collision force model. 32 Also, this method can simulate the collision process more accurate than the instantaneous impact model and continuous contact force model. 33 Base on previous studies, the first aim of this study is to use the finite element method to analyse the vibration response of the integral shroud blades for high-pressure steam turbine.…”
Section: Introductionmentioning
confidence: 99%
“…Yang and Huang [16] studied the longitudinal motion effects on the coupled vibration in a shaft-disk-blades system. Yang and Huang [17][18][19] investigated the coupling vibrations and applications among support-longitudinal, shaft-torsion, disktransverse, and blade-bending vibrations in a shaft-diskblades unit. Chiu and Huang [20] investigated the influence on coupling vibrations among shaft torsion, disk-transverse, and blade bending of a rotor system with a mistuned blade length analytically and found that the shaft-disk-blades system appeared to have four types of coupling vibrations: shaft-blade (SB), shaft-disk-blade (SDB), disk-blade (DB), and blade-blade (BB) mode.…”
Section: Introductionmentioning
confidence: 99%